PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MENTARI PERSADA DI JAKARTA - Sunarsi, Denok; Wijoyo, Hadion; Prasada, Dodi; Andi, Dede (Universitas Nusantara PGRI Kediri, 2020)
This study aims to determine the effect of the work environment on employee performance at PT. Mentari Persada in Jakarta. The method used is explanatory research with a sample of 98 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, the Work Environment variable obtained an average score of 3.43 with good criteria. Employee performance variables obtained an average score of 3.84 with good criteria. The work environment has a significant effect on employee performance with the regression equation Y = 8.431 + 0.876X, and a correlation value of 0.789 or strong with a determination of 62.2%. Hypothesis testing obtained a significance of 0.000 <0.05.